Model test to investigate failure mechanism and loading characteristics of shallow-bias tunnels with small clear distance - Lei, Ming-feng; Lin, Da-yong; Yang, Wei-chao; Shi, Cheng-hua; Peng, Li-min; Huang, Juan (Journal of Central South University, 2016)
Based on the similarity theory, a tunnel excavation simulation testing system under typical unsymmetrical loading conditions was established. Using this system, the failure mechanism of surrounding rock of shallow-bias tunnels with small clear distance was analyzed along with the load characteristics. The results show that: 1) The failure process of surrounding rock of shallow-bias tunnels with small clear distance consists of structural and stratum deformation induced by tunnel excavation; Micro-fracture surfaces are formed in the tunnel surrounding rock and extend deep into the rock mass in a larger density; Tensile cracking occurs in shallow position on the deep-buried side, with shear slip in deep rock mass. In the meantime, rapid deformation and slip take place on the shallow-buried side until the surrounding rocks totally collapse. The production and development of micro-fracture surfaces in the tunnel surrounding rock and tensile cracking in the shallow position on the deep-buried side represent the key stages of failure. 2) The final failure mode is featured by an inverted conical fracture with tunnel arch as its top and the slope at tunnel entrance slope as its bottom. The range of failure on the deep-buried side is significantly larger than that on the shallow-buried side. Such difference becomes more prominent with the increasing bias angle. What distinguishes it from the "linear fracture surface" model is that the model proposed has a larger fracture angle on the two sides. Moreover, the bottom of the fracture is located at the springing line of tunnel arch. 3) The total vertical load increases with bias angle. Compared with the existing methods, the unsymmetrical loading effect in measurement is more prominent. At last, countermeasures are proposed according to the analysis results: during engineering process, 1) The surrounding rock mass on the deep-buried side should be reinforced apart from the tunnel surrounding rock for shallow-buried tunnels with small clear distance; moreover, the scope of consolidation should go beyond the midline of tunnel (along the direction of the top of slope) by 4 excavation spans of single tunnel. 2) It is necessary to modify the load value of shallow-bias tunnels with small clear distance.